An investigation on perceived constraints of teachers in relation to leisure activities - Adnan Ersoy; Halil Bisgin; Umit Dogan Ustun (Türk Spor ve Egzersiz Dergisi)
This paper examines perceived constraints of physical education and other branches teachers (music/arts) in relation to leisure activities. After legal permissions 228 teachers, who work in city center Kütahya (a city in the west part of Turkey), voluntarily participated in the study. Leisure Constraints Scale-18- was used to collect data. To analyze the data in addition to descriptive statistics such as mean and standard deviation, Mann Whitney U was used. According to findings of the study while "time" was found to be the most important factor, "lack of interest" was found to be the least important factor as leisure constraints for all participants jointly. Also, analyze results revealed that while physical education and sports teachers are more constrained by intrapersonal factors other branch teachers are constrained by interpersonal factors.